2007
DOI: 10.1021/ac0706527
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Detection of a Model Analyte in Serum by a Gold Nanorod Sensor

Abstract: We describe the fabrication of a label-free, chip-based biosensor based on the localized surface plasmon resonance (LSPR) of gold nanorods. Gold nanorods were chemisorbed onto a mercaptosilane-modified glass substrate, followed by conjugation of biotin to the nanorods. Streptavidin binding to biotin was monitored by the wavelength shift of the LSPR peak in the UV-vis extinction spectrum of the immobilized gold nanorods due to the change in local refractive index at the gold nanorod surface induced by streptavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
283
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(305 citation statements)
references
References 38 publications
14
283
3
1
Order By: Relevance
“…Secondly, the height of analytical response was inverse related to the affinity of the respective antibodies, which was consistent with the inversely proportional relationship between antibody affinity and binding capacity [20]. Since then, numerous labs have put effort into the work for correlating peak intensity and position of the surface plasmon absorbance of GNPs with the local refractive index of the surrounding medium [21][22][23][24][25][26][27][28][29][30][31], which is termed the localized surface Plasmon resonance (LSPR).…”
Section: Gnp-based Optical Biosensorsmentioning
confidence: 53%
“…Secondly, the height of analytical response was inverse related to the affinity of the respective antibodies, which was consistent with the inversely proportional relationship between antibody affinity and binding capacity [20]. Since then, numerous labs have put effort into the work for correlating peak intensity and position of the surface plasmon absorbance of GNPs with the local refractive index of the surrounding medium [21][22][23][24][25][26][27][28][29][30][31], which is termed the localized surface Plasmon resonance (LSPR).…”
Section: Gnp-based Optical Biosensorsmentioning
confidence: 53%
“…Among these geometries, nanorod is particularly interesting to us, because it provides an excellent platform with well-defined absorption spectrum for a labelfree bioanalytical assay [13][14][15][16][17][18]. The optical transduction by Au nanorods (GNRs) is based upon the phenomenon of localized surface plasmon resonance, that is, nanoSPR (or LSPR) [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…4). It revealed that AgPLs@Au exhibit superior sensitivity to AgPLs prepared by colloidal lithography (19 nm RIU -1 ) 26 and AuNRs (231, 15 252, 27 and 206 28 nm RIU -1 ) even after TiO2-coating with the thermal stability. Although the sensitivity of the TiO2-coated AgPL@Au-deposited glass substrate decreased after TiOxovercoating with the chemical stability, the substrate could show satisfactory performance of LSPR sensing.…”
Section: Resultsmentioning
confidence: 99%